Inflammatory myofibroblastic tumor of the urinary bladder: A diagnostic challange and therapeutic dilemma - Singh, Aneeta (Int J Appl Basic Med Res, 2015)
Inflammatory myofibroblastic tumor (IMT) is a rare, aggressive tumor of indeterminate malignant potential with myofibroblastic differentiation. Though bladder location is very uncommon, it arises from the bladder submucosal stroma as a polypoidal growth and is easily mistaken for a malignant neoplasm- clinically, radiologically and histologically. Essential criteria for the diagnosis of IMT are: spindle myoepithelial cell proliferation and lymphoplasmacytic infiltrate. Here we report the case of a 30 years old man who presented with painless gross haematuria for 2 weeks. The patient underwent open partial cystectomy and the final pathological diagnosis was IMT of bladder.